胰岛素样生长因子受体基因单核苷酸多态性与晚期非小细胞肺癌铂类化疗疗效及预后的研究 (Zhongguo Fei Ai Za Zhi, 2012)
BACKGROUND AND OBJECTIVE: It has been proven that the insulin-like growth factor 1 receptor (IGF-1R) gene is an important regulator of many aspects of growth, differentiation, and development. The insulin-like growth factor 2 receptor (IGF-2R) gene is a negative mediator for carcinogenesis. The aim of this study is to investigate the relationship of IGF-1R+1013(G/A) and IGF-2R+1619(G/A) single nucleotide polymorphism (SNP) with platinum-based chemotherapy outcomes in advanced non-small cell lung cancer (NSCLC). METHODS: A total of 132 patients with NSCLC were routinely treated with platinum-based chemotherapy, and their clinical responses were evaluated after four cycles of chemotherapy. IGF-1R+1013(G/A) and IGF-2R+1619(G/A) were genotyped using polymerase chain reaction-restrictive fragment length polymorphism. The relationship between IGF-1R+1013(G/A) and IGF-2R+1619(G/A) genotypes and the clinical benefit rate, as well as the median survival time (MST), was analyzed. RESULTS: No significant association was found between IGF-1R+1013(G/A) and IGF-2R+1619(G/A) polymorphisms with clinical benefit (P > 0.05). Further, we found that the two SNPs could not work together (P=0.975). The MST of patients with IGF-1R+1013(G/A) genotypes with A allele (GA+AA) was significantly shorter than that of GG genotype carriers (P=0.017). There was no significant difference in MST in patients with IGF-2R+1619(G/A) A allele (GA+AA) carrier and GG genotype carrier (P=0.575). The two SNPs showed a synergistic effect on MST. Patients who carried a mutant allele A of IGF-1R+1013(G/A) and a mutant allele A of IGF-2R+1619(G/A) had a MST of 12 months, which was significantly shorter than that of patients with other genotypes (P < 0.05). Estimation by the Cox proportional hazards model showed that IGF-1R+1013(G/A) polymorphism is an independent prognostic factor (P=0.020), and IGF-1R+1013(G/A) polymorphism in combination with IGF-2R +1619(G/A) polymorphism is an independent prognostic factor in advanced NSCLC (P=0.025). CONCLUSION: IGF-1R+1013(G/A) polymorphism alone or in combination with IGF-2R +1619(G/A) polymorphism was associated with the overall survival period in patients with advanced NSCLC after treatment with platin-based chemotherapy, which might be a prognostic factor in platin-treated patients with advanced NSCLC.